Peningkatan Aktivitas Dan Hasil Belajar Siswa Melalui Implementasi Pembelajaran Dengan Hybrid Text-Book - Jayantika, I Gusti Agung Ngurah Trisna; Pramesti, Kadek Nicelia; Dewi, Putu Dian Karlina (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
Monotonous learning methods, such as long lectures, repetition of material without variety, and lack of engaging interaction, can cause students to feel bored and unmotivated to pay attention or understand the material being taught. This study aims to assess the extent to which the implementation of hybrid text-books in the learning process can increase the level of student involvement in learning, while improving their learning outcomes. This research is a classroom action research (PTK) conducted with the aim of improving student learning outcomes of class XI G at SMA N 2 Mengwi, which has 38 students.. This research method consists of two cycles, where each cycle consists of four meetings. Analysis of learning outcomes in each cycle resulted in the percentage of students who successfully achieved or exceeded the minimum completeness criterion score of 75. The results showed that the average score of all students at the Pre-Cycle stage was 50.15; the average overall score of students at the Cycle I stage reached 72.07; The average overall score of students in Cycle II also showed a significant improvement, reaching 80.92. The implications of this study highlight the importance of utilizing technology, such as hybrid textbooks, in improving student engagement and teacher teaching effectiveness to create inclusive and adaptive learning environments.